2021
DOI: 10.1021/acs.inorgchem.1c00461
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Cationic Group 4 Metallocene Complexes Stabilized by Pendant N-Donor Groups

Abstract: Cationic group 4 metallocene complexes with pendant imine and pyridine donor groups were prepared as stable crystalline [B­(C6F5)4]− salts either by protonation of the intramolecularly bound ketimide moiety in neutral complexes [(η5-C5Me5)­{η5-C5H4CMe2CMe2C­(R)N-κN}­MCl] (M = Ti, Zr, Hf; R = t-Bu, Ph) by PhNMe2H+[B­(C6F5)4]− to give [(η5-C5Me5)­{η5-C5H4CMe2CMe2C­(R)NH-κN}­MCl]+[B­(C6F5)4]− or by chloride ligand abstraction from the complexes [(η5-C5Me5)­(η5-C5H4CMe2CH2C5H4N)­MCl2] (M = Ti, Zr) by Li­[B­(C6F5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 98 publications
5
17
1
Order By: Relevance
“…As in our previous contributions, 48,50 we found that the experimentally observed emission of the studied compounds originates from S83 and S84), all with rather poor or even negligible quantum yields of emission, exhibit non-negligible contributions of the PPh 2 (�E) (E = O, S, Se) moiety to the 3 LMCT transition. Comparing these trends with the observed luminescence quantum yields leads us yet again 48 to the conclusion that the most efficient S n → T 1 intersystem crossing and subsequent T 1 → S 0 emission is found in cationic complexes with the most localized LMCT transitions (in complexes 3/4 containing HOMO-polarizing Cp* ligands). On a final note, the auxiliary P�E (E = O, S, Se) ligand is a suitable group for modifying spin−orbit coupling in our cationic complexes, as it does not significantly shift the transition energy, yet introduces mass into the proximity of the central atom where the 3 LMCT SOMO is localized.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…As in our previous contributions, 48,50 we found that the experimentally observed emission of the studied compounds originates from S83 and S84), all with rather poor or even negligible quantum yields of emission, exhibit non-negligible contributions of the PPh 2 (�E) (E = O, S, Se) moiety to the 3 LMCT transition. Comparing these trends with the observed luminescence quantum yields leads us yet again 48 to the conclusion that the most efficient S n → T 1 intersystem crossing and subsequent T 1 → S 0 emission is found in cationic complexes with the most localized LMCT transitions (in complexes 3/4 containing HOMO-polarizing Cp* ligands). On a final note, the auxiliary P�E (E = O, S, Se) ligand is a suitable group for modifying spin−orbit coupling in our cationic complexes, as it does not significantly shift the transition energy, yet introduces mass into the proximity of the central atom where the 3 LMCT SOMO is localized.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…Methods applied in our quantum chemical study were adapted from our previously established computational protocol. 48,50 Optimized molecular geometries (1, 2-O, -S, -Se, and 6) and geometries of lone cations (3/4-O, -S, -Se, and 7) were in good agreement with the XRD-determined solid-state structures, where available (see the Supporting Information, Chapter 5.3). Calculated transition energies (Table 3 and Supporting Information, Chapter 5.2) corresponded well to the experimentally observed absorption bands in solution and emission wavelengths in the solid state (cf.…”
Section: ■ Results and Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The most effective molecular photosensitizers for photocatalytic and photovoltaic applications broadly absorb visible light , and exhibit suitably long-lived charge-transfer (CT) excited states for efficient charge injection into semiconductor surfaces or amassing sufficient concentrations of reactive excited states for synthesis . Coordination complexes of precious metals in low oxidation states such as Ru­(II) or Ir­(III) with chelating, π-acceptor ligands can fulfill these criteria effectively, but cost and scarcity considerations have driven the search for chromophores based on more abundant materials that do not compromise on performance. , While creative ligand designs have enabled the development of an increasing number of exciting candidates based on Cu, , Zr, Co, , and Cr, iron has long represented a key target in this area . The realization of useful Fe­(II)-based photosensitizers, however, has been stymied by the inherent tendency of first-row transition metal complexes to undergo rapid deactivation of CT excited states via lower-lying metal-centered (MC) states .…”
Section: Introductionmentioning
confidence: 99%
“…Recent applications of the NTO method have been primarily in photochemistry and -physics and studies of excited states. A small selection of available studies is presented by refs . Visualization of NTOs has been particularly useful for systems for which the descriptions of an electronic transition of interest involve a considerable number of pairs of occupied and unoccupied MOs with relatively low weights, which renders the assignment of the excitation difficult.…”
Section: Introductionmentioning
confidence: 99%